Single Crystals of KRE(MoO4)2, (RE‐ Ce, Pr) Obtained from Fluorides: Scheelite‐Related Structure and Luminescence. Issue 12 (13th November 2017) - Terebilenko, Kateryna V.; Bychkov, Konstantin L.; Klymyshyna, Kateryna E.; Baumer, Vyacheslav N.; Slobodyanik, Mykola S.; Khomenko, Elena V.; Dotsenko, Volodymir P.
Abstract: Single crystals of double molybdates KRE(MoO4 )2 (RE = Ce and Pr) have been prepared from high‐temperature melts by a facile and effective fluoride‐assisted method, and investigated by XRD, FTIR and photoluminescence (PL) spectroscopy. The results showed that the molar ratio of K/Mo in the molten solution play an important role in controlling content of the crystalline products. The crystallization fields of KCe(MoO4 )2 has been found avoiding oxides admixtures. Both tetragonal scheelite‐related crystal structures have been established by means of single crystal X‐Ray diffraction. Structural motif of KPr(MoO4 )2 has been established for the first time, while KCe(MoO4 )2 has been reinvestigated and its crystal structure data have been refined. The excitation and emission spectra of KPr(MoO4 )2 have been discussed in a light of energy transfer from a molybdate host. Abstract : Using fluorides as a source of lanthanides(III) in the high‐temperature melt method yields single crystals of double potassium molybdates containing cerium(III) or praseodimium(III). The key factor in pure single crystals preparation is molar ratio of K/Mo in the molten solution. Both compounds reveal scheelite‐type structure and crystallize tetragonally with the space group I41/a and two formula units per unit cell. The KPr(MoO4 )2 crystals possess red photoluminescence under excitations in ultraviolet and visible spectral regions.